Circus-specific extension of the International Olympic Committee 2020 consensus statement: methods for recording and reporting of epidemiological data on injury and illness in sport. Issue 3 (13th September 2022) - Greenspan, Stephanie; Munro, David; Nicholas, Joanna; Stubbe, Janine; Stuckey, Melanie I; Van Rijn, Rogier M
Abstract : Indepth knowledge of injury and illness epidemiology in circus arts is lacking. Comparing results across studies is difficult due to inconsistent methods and definitions. In 2020, the International Olympic Committee (IOC) consensus group proposed a standard method for recording and reporting epidemiological data on injuries and illnesses in sports and stated that sport-specific extension statements are needed to capture the context of each sport. This is the circus-specific extension to be used with the IOC consensus statement. International circus arts researchers in injury and illness epidemiology and performing arts medicine formed a consensus working group. Consensus statement development included a review of literature, creation of an initial draft by the working group, feedback from external reviewers, integration of feedback into the second draft and a consensus on the final document. This consensus statement contains circus-specific information on (1) injury definitions and characteristics; (2) measures of severity and exposure, with recommendations for calculating the incidence and prevalence; (3) a healthcare practitioner report form ; (4) a self-report form capturing health complaints with training and performance exposure ; and (5) a demographic, health history and circus experience intake questionnaire . This guideline facilitates comparing results across studies and enables combining data sets on injuries in circus arts. This guideline informs circus-specific injury prevention, rehabilitation, and risk management to improve the performance and health of circus artists.